Paving the Way for Recognizing Postpenetration Rape Through the Mistake of Fact Defense - King, Katherine M. (2020)
On February 13, 2019, the Massachusetts Supreme Judicial Court in Commonwealth v. Sherman introduced a communication element in rape cases involving withdrawn consent. The prosecutor must prove that the victim communicated the revocation of consent such that a reasonable defendant would understand its withdrawal. In doing so, the court invoked a mistake of fact defense with regard to consent, which Massachusetts historically did not apply in its rape jurisprudence. This Comment notes that Massachusetts is unique in recognizing postpenetration rape as a legal possibility. This Comment compares Sherman to the Supreme Judicial Court’s decision in 2008 in Commonwealth v. Blache. In Blache, the court made the mistake of fact defense available to the defendant when the victim was incapacitated and thus could not consent. By comparing Sherman to Blache, this Comment further argues that the mistake of fact defense in cases of postpenetration rape does not expand Massachusetts’ principle that the mistake of fact defense should not apply in most rape cases